EFFISIENSI PEMILIHAN SUPPLIER MENGGUNAKAN METODE FUZZY â DATA ENVELOPMENT ANALYSIS (DEA) - Adraintantri, Emmalia; Priyasmanu, Thomas (DINAMIKA DOTCOM, 2018)
A company is required to fulfil customerâs need in terms of quality and quantity, resulting in a streamlined production. Therefore, a company must ensure the supply of raw materials to be perfect, delivery must be on time, the quality and quantity must be confirmed. In conclusion, the accuracy of the selection of suppliers is crucial to determine whether or not the supply of raw materials of the company. The purpose of this research is to create an application to assess the suppliers efficiency to be a raw material supplier based on several criteria. The specific targets in this research is to help a company on decidingÂ  which supplier is efficient enough to choosen, rapidly and precisely. Because by making this computer applications, the calculation process for supplier selection is done quickly with high accuracy, considering the are a lot of number of criteria that must be considered to determine the performance of suppliers where alternative suppliers are not small, with products or raw materials purchased even in types and quantities are not few. The methods used in achieving these goals are Fuzzy and DEA (Data Envelopment Analysis) methods that are integrated into a computer application. The outcome is to acknowledge which supplier is efficient Â to be chosen as a partner. Therefore by using this application, then the long calculation process can be done faster and better accuracy.Â Keywords: Efficiency, Supplier, Fuzzy-DEA